Serum total homocysteine, folate, 5,10-methylenetetrahydrofolate reductase (MTHFR) 677C→T genotype and subclinical atherosclerosis - Panayiotou, Andrie G.; Nicolaides, Andrew N.; Griffin, Maura B.; Tyllis, Theodosis K.; Georgiou, Niki; Martin, Richard M.; Bond, Dawn; Tziakouri-Shiakalli, Chrysa; Fessas, Charis H.; Constantinou-Deltas, Constantinos D. (My University, 2009)
Objective : To determine the relationship of serum total homocysteine (tHcy), serum folate and 5,10-methylenetetrahydrofolate reductase (MTHFR) 677C→T genotype with ultrasonic arterial wall measurements associated with subclinical atherosclerosis. Study design : Cross-sectional analysis of 767 participants in an ongoing prospective study. Intima-media thickness (IMT) of the common carotid (IMTcc), IMT of the internal carotid including plaque when present (IMTmax) and the sum of the thickest plaques present in both carotid and both common femoral bifurcations (total plaque thickness (TPT)) were measured using ultrasound. Results : People in the upper homocysteine quartile were more likely to have clinical cardiovascular disease (CVD) than those in the lowest three quartiles. They were also more likely to have plaques. The MTHFR 677C→T genotype was not associated with any of the measures of subclinical atherosclerosis in either men or women but was the most important determinant of total homocysteine levels in men under 60 years of age. Conclusions : Increased homocysteine levels but not MTHFR 677C→T genotype, are associated with subclinical atherosclerosis and the presence of plaques. Our results indicate that measurements of blood levels of homocysteine and folate in people at intermediate risk for atherosclerotic CVD before symptoms occur, might improve risk stratification and facilitate the decision to provide folate/B vitamin intervention in primary prevention.
Keywords: Folate; Homocysteine; IMT; MTHFR; Subclinical atherosclerosis; Ultrasound